The impact of distance cataract surgical wet laboratory training on cataract surgical competency of ophthalmology residents - Amelia Geary; Qing Wen; Rosa Adrianzén; Nathan Congdon; R. Janani; Danny Haddad; Clare Szalay Timbo; Yousuf M. Khalifa (BMC Medical Education, 2021)
Abstract Background This study assessed the impact of distance cataract surgical wet laboratory training on surgical competency of ophthalmology residents at a tertiary-level ophthalmic training center in Trujillo, Peru. Methods Three five-week distance wet lab courses were administered through Cybersight, Orbis International’s telemedicine platform. Weekly lectures and demonstrations addressed specific steps in phacoemulsification surgery. Each lecture had two accompanying wet lab assignments, which residents completed and recorded in their institution’s wet lab and uploaded to Cybersight for grading. Competency was assessed through anonymous grading of pre- and post-training surgical simulation videos, masked as to which occurred before and after training, using a standardized competency rubric adapted from the Ophthalmology Surgical Competency Assessment Rubric (OSCAR, scale of 0–32). Day one best-corrected post-operative visual acuity (BVCA) was assessed in the operative eye on the initial consecutive 4–6 surgeries conducted by the residents as per the norms of their residency training. An anonymous post-training satisfaction survey was administered to trainees’. Results In total, 21 ophthalmic residents participated in the courses, submitting a total of 210 surgical videos. Trainees’ average competency score increased 6.95 points (95%CI [4.28, 9.62], SD = 5.01, p < 0.0001, two sample t-test) from 19.3 (95%CI [17.2, 21.5], SD = 4.04) to 26.3 (95%CI [24.2, 28.3], SD = 3.93). Visual acuity for 92% of post-training resident surgeries (n = 100) was ≥20/60, meeting the World Health Organization’s criterion for good quality. Conclusions Structured distance wet lab courses in phacoemulsification resulted in significantly improved cataract surgical skills. This model could be applicable to locations where there are obstacles to traditional in-person training, such as the current COVID-19 pandemic.